Integrated Governance: Achieving Governance Results and Contributing to Sector Outcomes - Frazer, Sarah; Granius, Mark; Brinkerhoff, Derick W.; McGregor, Lisa (RTI Press Publication, 2022)
Achieving broad-based socio-economic development requires interventions that bridge disciplines, strategies, and stakeholders. Effective sustained progress requires more than simply an accumulation of sector projects, and poverty reduction, individual wellbeing, community development, and societal advancement do not fall neatly into sectoral categories. However, researchers and practitioners recognize key operational challenges to achieving effective integration that stem from the structures and processes associated with the current practice of international development. Integration calls for the intentional linking of intervention designs, implementation, and evaluation across sectors and disciplines to achieve mutually reinforcing outcomes. In this report, we summarize the results of a study we conducted to explore the challenges facing governance programs that integrate with sector interventions to achieve governance outcomes and contribute to sector outcomes. Through a review of policy documents and project reports from recent integrated governance programs and interviews with donor and practitioner staff, we found three integrated governance programming variants, an emphasis on citizen and government collaboration to improve service delivery, interventions that serve as the glue between sectors, and a balancing act for indicators to measure contribution to sectoral outcomes. Our analysis identified four key success factors: contextual readiness, the application of learning and adapting approaches, donor support, and recognition of the limitations of integrated governance. We then discuss recommendations and implications and for answering the challenge of integrating governance and sector programming to achieve development outcomes.

Seeing the Combined Effects of Aid Programmes - Burge, Richard; Nadelman, Rachel; McGee, Rosie; Fox, Jonathan; Anderson, Colin (IDS Policy Briefing, 2022)
Multiple aid agencies often try to support change in the same places, at the same time, and with similar actors. Surprisingly, their interactions and combined effects are rarely explored. This Policy Briefing describes findings from research conducted on recent aid programmes that overlapped in Mozambique, Nigeria, and Pakistan, and from a webinar with UK Foreign, Commonwealth & Development Office (FCDO) advisors and practitioners. The research found three distinct categories of ‘interaction effects’: synergy, parallel play, and disconnect. We explore how using an ‘interaction effects’ lens in practice could inform aid agency strategies and programming.

Evaluating complex interventions: What are appropriate methods? - Masset, Eduardo (CEDIL, 2022)
In the CEDIL Methods brief, ‘Evaluating complex interventions: What are appropriate methods?’ we identify four types of complex development interventions: long causal chain interventions, multicomponent interventions, portfolio interventions, and system-level interventions. These interventions are characterised by multiple activities, multiple outcomes, multiple components, a high level of interconnectedness, and non-linear outcomes.